DEMODULATOR THAT CONVERTS ENCODER STEREO SIGNAL INTO L AND R AUDIO SIGNAL - Ibrahim Ashari; Faisol Ahmad (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
As technology develops in today’s age, there are many radio equipment easily found in the market. Certainly, there is a stereo decoder module inside a FM radio receiver which operates to return radio signal that previously was modulated and broken apart into stereo audio signal (L+R) and (L-R). There are many stereo decoders already presented inside FM radio receivers. Based on this premise, there is a problem that can be studied, which is how to design a decoder stereo in a stereo FM radio receiver that functions as the demodulation in stereo FM radio and operates to release L+R audio signal to a receiver radio. Therefore, it needs a signal demodulatorof encoder stereo that converts L and R audio signal. Based on the testing result, it showed that sideband frequency from the result of DSB-SC demodulator process, which was produced through R and L channels, still had frequency value differences with average percentage of 1.416% out of the expected frequency value. This was due to the frequency oscillator from the generator function.